1996
DOI: 10.1073/pnas.93.2.809
|View full text |Cite
|
Sign up to set email alerts
|

Sodium: a male moth's gift to its offspring.

Abstract: Males of the moth Gluphisia septentrionis acquire sodium by drinking from mud puddles. Analyses of male and female bodies indicate that such "puddling" behavior enables the male to provide his mate with a nuptial gift of sodium, presumably via the spermatophore. This gift (about 10 pg), amounting to more than half of a puddler male's total body sodium, is in large measure apportioned by the female to her eggs. Puddler-sired eggs contain 2 to 4 times more sodium than those control-sired; this difference is alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 13 publications
4
49
0
Order By: Relevance
“…Researchers showed that different families of butterflies have preference of up-taking various salts and amino acids from various puddle sources. Members of Papilionidae and Pieridae more often visited NaCl rich sources and members of Nymphalidae, Hesperiidae and Lycaenidae preferred amino acid rich sources (Beck et al, 1999, Lai-Fook 1991, Pivnick & McNeil, 1987, Smedley & Eisner, 1995, 1996. In the present study results showed that the members of Papilionidae and Pieridae were preferred mineral sources as they did puddle on mostly water sources (mud, wet soil, wet sand, wet brick) while members of Nymphalidae, Hesperiidae and Lycaenidae were preferred to puddle on various nutrient sources (carrion, dung, rotten flowers) (Gilbert 1972, Alm et al, 1990, Erhardt & Rusterholz 1998, O'Brien et al, 2005.…”
Section: Bank Of Bangshi Riversupporting
confidence: 56%
See 1 more Smart Citation
“…Researchers showed that different families of butterflies have preference of up-taking various salts and amino acids from various puddle sources. Members of Papilionidae and Pieridae more often visited NaCl rich sources and members of Nymphalidae, Hesperiidae and Lycaenidae preferred amino acid rich sources (Beck et al, 1999, Lai-Fook 1991, Pivnick & McNeil, 1987, Smedley & Eisner, 1995, 1996. In the present study results showed that the members of Papilionidae and Pieridae were preferred mineral sources as they did puddle on mostly water sources (mud, wet soil, wet sand, wet brick) while members of Nymphalidae, Hesperiidae and Lycaenidae were preferred to puddle on various nutrient sources (carrion, dung, rotten flowers) (Gilbert 1972, Alm et al, 1990, Erhardt & Rusterholz 1998, O'Brien et al, 2005.…”
Section: Bank Of Bangshi Riversupporting
confidence: 56%
“…On sunny days, after rain butterfly gather for puddle. The main reason for visiting puddle is to get nutrients mainly sodium (Na) (Arms et al, 1974, Pivnick & McNeil, 1987, Smedley & Eisner, 1995, 1996. Besides, up taking Sodium, they also get other nutrients like amino acids (Arms et al, 1974, Boggs & Gilbert, 1979 and other salts like calcium phosphate (Lai-Fook 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Monarchs reared on roadside milkweed had significantly more sodium in their abdomen than those reared on control milkweed. Given the importance of sodium in Lepidopteran mating (41)(42)(43) and egg production (60), it is possible that the increased abdominal sodium may directly translate into differences in fitness, such as spermatophore size or egg number (61). Although the levels of sodium that we measured in butterfly tissue were similar to those Fig.…”
Section: Implications: Changes In Limited Nutrients and Selection On mentioning
confidence: 57%
“…Sodium availability has been shown to affect the development and activity of flight muscle in male Lepidoptera (37)(38)(39). Many adult male Lepidoptera actively forage for sodium through puddling, transferring much of this sodium to females during mating (23,(40)(41)(42)(43). In addition, host plants of many butterfly species commonly grow along roadsides and would be affected by roadside runoff.…”
mentioning
confidence: 99%
“…Leather, 1984;Wei et al, 1998;Fischer et al, 2004;O'Brien et al, 2004;Bauerfeind and Fischer, 2005b), the role of most other adult-derived substances is still only partially resolved (e.g. DunlapPianka et al, 1977;Murphy et al, 1983;Moore and Singer, 1987;Hill and Pierce, 1989;Boggs and Jackson, 1991;Smedley and Eisner, 1996).…”
Section: Introductionmentioning
confidence: 99%